Convalescent plasma therapy, COVID-19, infectious disease - Sumayyah Annida; Dian Isti Angraini (CV. Jasa Sukses Abadi, 2020)
Acute diarrhea is still a major cause of child morbidity and mortality in developing countries. One national data study reported that Lampung Province contributed 32.148 cases of diarrhea in 2018. Most cases of diarrhea were found in the age group 5-14 years followed by the age group of 15-24 years, and women were more often stricken with diarrhea than men. To identify internal and external risk factors and clinical problems in patients, as well as holistically manage patients by applying family doctors according to evidence based medicine through a patient centered approach and family approach. This study analysis is a case report. Primary data were obtained through history taking (autoanamnesis from the patient and alloanamnesis from the patient's family) physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment is based on a holistic diagnosis from the beginning, process, and end of study in a qualitative and quantitative manner. Patient An. NO, 5 years old, has been diagnosed with acute diarrhea without dehydration, has a concern about the declining health condition with a liquid chapter that does not stop. Limitations of the patient's family knowledge of the patient’s disease (cause, mode of transmission, the risk of the risk factors, treatment, and complications), use of unclean water for cooking and not paying attention to food hygiene are the main factors of the problem. Holistic and comprehensive management of patients' problems An. NO has been done by providing counseling to improve patient and family knowledge of diarrheal diseases and clean and healthy life.